2021
DOI: 10.1002/cbic.202100631
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembling Properties and Recovery Effects on Damaged Skin Cells of Chemically Synthesized Mannosylerythritol Lipids

Abstract: Mannosylerythritol lipids (MELs), which are one of the representative sugar‐based biosurfactants (BSs) produced by microorganisms, have attracted much attention in various fields in the sustainable development goals (SDGs) era. However, they are inseparable mixtures with respect to the chain length of the fatty acids. In this study, self‐assembling properties and structure‐activity relationship (SAR) studies of recovery effects on damaged skin cells using chemically synthesized MELs were investigated. It was r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It was found that compound 22 , which exhibited almost no recovery effect, did not show a CAC value in the tested concentration range due to its low surface activity. The CAC value for 23 , which exhibited a moderate recovery effect, was higher than that for MEL‐D 18 (1.7×10 −5 M) [7] at 2.7×10 −5 M due to its hydrophilicity. On the other hand, the CAC value for 24 , which exhibited an excellent recovery effect, was lower than that for 18 at 1.1×10 −5 M due to its hydrophobicity, suggesting that 24 was easily absorbed at lower concentrations into the intercellular spaces of the stratum corneum [16] .…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…It was found that compound 22 , which exhibited almost no recovery effect, did not show a CAC value in the tested concentration range due to its low surface activity. The CAC value for 23 , which exhibited a moderate recovery effect, was higher than that for MEL‐D 18 (1.7×10 −5 M) [7] at 2.7×10 −5 M due to its hydrophilicity. On the other hand, the CAC value for 24 , which exhibited an excellent recovery effect, was lower than that for 18 at 1.1×10 −5 M due to its hydrophobicity, suggesting that 24 was easily absorbed at lower concentrations into the intercellular spaces of the stratum corneum [16] .…”
Section: Resultsmentioning
confidence: 73%
“…When β‐GlcEL‐D 22 with all substituents in the equatorial position was used, micrometer‐sized solid aggregates containing hydrophobic Nile red were observed, probably because 22 was prone to interact intermolecularly (Figure 2a). In sharp contrast, when other MEL analogues 23 and 24 with at least one substituent in the axial position were used, it was found that Nile red was localized at the membrane boundary, and giant vesicles were spontaneously generated as for MEL‐D 18 [7] (Figure 2b and c). These results clearly indicated that slight differences in the steric configuration of a hydrophilic erythritol moiety and hydrophobic fatty acyl chains affect the ability to form vesicles.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, they exhibit anti-bacterial, anti-cancer, and anti-oxidative activities 2−6) . One of the MEL producer Pseudozyma tsukubaensis produces a diastereomer type of MEL-B 7) at high levels (>70 g/L from olive oil 8) ) and with the demonstrated ability to repair damaged skin and hair 6,9,10) . Accordingly, MEL-B has been commercialized in the cosmetics industry for over a decade.…”
mentioning
confidence: 99%